Cardiac Autonomic Modulation and Response to Sub-Maximal Exercise in Chilean Hypertensive Miners - Lang, Morin; Mendt, Stefan; Paéz, Valeria; Gunga, Hanns-Christian,; Bilo, Grzegorz; Merati, Giampiero; Parati, Gianfranco; Maggioni, Martina Anna (Frontiers in Physiology, 2022)
Cardiac autonomic modulation in workers exposed to chronic intermittent hypoxia (CIH) has been poorly studied, especially considering hypertensive ones. Heart rate variability (HRV) has been proven as valuable tool to assess cardiac autonomic modulation under different conditions. The aim of this study is to investigate the cardiac autonomic response related to submaximal exercise (i.e., six-minute walk test, 6MWT) in hypertensive (HT, n=9) and non-hypertensive (NT, n=10) workers exposed for > two years to CIH. Participants worked on 7-on 7-off days shift between high altitude (HA: > 4.200 m asl) and sea level (SL: < 500 m). Data were recorded with electrocardiography (ECG) at morning upon awakening (10 min supine, baseline), then at rest before and after (5 min sitting, pre and post) the 6MWT, performed respectively on the first day of their work shift in HA, and after the second day of SL sojourn. Heart rate was higher at HA in both groups for each measurement (mixed effects model, p < 0.01). Parasympathetic indices of HRV were lower in both groups at HA, either in time domain (RMSSD, p < 0.01) and in frequency domain (log HF, p < 0.01), independently from measurement’s time. HRV indices in non-linear domain supported the decrease of vagal tone at HA and showed a reduced signal’s complexity. ECG derived respiration frequency (EDR) was higher at HA in both groups (p < 0.01) with interaction group x altitude (p = 0.012), i.e., higher EDR in HT with respect to NT. No significant difference was found in 6MWT distance regarding altitude for both groups, whereas HT covered a shorter 6MWT distance compared to NT (p<0.05), both at HA und SL. Besides, conventional arm-cuff blood pressure and oxygen blood saturation values (recorded before, at the end and after 5-min recovery from 6MWT), reported differences related to HA only. HA is the main factor affecting cardiac autonomic modulation, independently from hypertension. However, presence of hypertension was associated with a reduced physical performance independently from altitude, and with higher respiratory frequency at HA.